Application of Eco-Democracy to Environmental Legal Protection Post-Mining Reclamation in Indonesia - Zulfatah, Zulfatah; Hidayati, Hidayati; Nur Hidayah, Andi (Jurnal Impresi Indonesia, 2024)
Mining in Indonesia still leaves many excavation holes that have not been reclaimed, at least 8 million hectares of post-mining land after the use of coal mining land in East Kalimantan Province. As a result, from 2011 to 2018, 32 people died, most of them children, while 140 people died in all regions in Indonesia due to drowning in ex-mining holes. The aim of this research is to provide legal protection for land through the application of the Eco-Democracy concept due to violations by fraudulent entrepreneurs. The method used is the approach of statutory opposition and conceptual opposition of regulations relating to legal issues resolved through a statutory approach. The results of the research explain that reviewing all laws written in Government Regulation Number 78 of 2010 concerning Reclamation and Post-Mining and Number 4 of 2009 in the Republic of Indonesia Law concerning Mineral and Coal Mining requires companies to restore land through reclamation after the mining process is complete. Prepare collateral in the form of money given by businesses committed to restoring and improving the land environment. The government authority will supervise the reclamation during its implementation so that mining entrepreneurs will comply and not abandon the ex-mining land.